The Principle of Iknemook for Mediator in Medical Malpractice Dispute Settlement Through Mediation - Made Wirya Darma; I Gusti Agung Ayu Mas Triwulandari; I Gede Agus Kurniawan (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2020)
The agreement is made to undertake a treatment for an illness, which resulted in the conclusion of a therapeutic contract under Laws as regulated under Article 1233 of the Civil Code of Indonesia (Kitab Undang-Undang Hukum Perdata). Every legal relationship will result in rights and obligations. Medical malpractice is usually caused by an unfulfillment of a patient’s basic rights because of the lack of communication or information, which are the basic rights of a patient. The dispute settlement through court system is unsatisfactory for either patient or doctor. Therefore, a dispute settlement that is considered ideal is through non-litigation process, which is mediation, to achieve win-win solution. Procedures for mediators to mediate such malpractice dispute are in accordance to seven principles, which are also regarded as the seven bbaasic philosophies of mediation for medical dispute, which are known as the principle of Iknemook. The contents of the Iknemook principle for mediator in medical malpractice dispute settlement through mediation are the problems in this research. This research aims to assess and study the seven principles of Iknemook for mediator in medical malpractice dispute settlement through mediation. This research is categorised as a library research with a specification of descriptive research, which is presented to explain Iknemook principles for mediator in medical malpractice dispute settlement through mediation. This research finds that the principles comprised of the principles of good faith of both parties, trust, neutrality, exclusivity of a mediator (med-power), open-mind, autonomy, and confidentiality.